Does privatization deliver? : highlights from a World Bank conference - Galal, Ahmed; Shirley, Mary M.; World Bank. (Washington, D.C. : World Bank, 1994)
The book summarizes the discussions at a recent world bank Conference on the welfare effects of privatization.
Includes bibliographical footnotes and index.
osc 31/08/2016
Loans
Keywords: Privatization; Public sector $1 (BPrivatisation.s